Design-Based Research as Professional Development: Results of Prospective Teachers' Participation in the Development of Electrical Circuit Augmented Reality Sites for Students to Increase Scientific Thinking Skills - Putri Dwi Agustiningrum; Wirawan Fadly; Primus Demboh (Universitas Pendidikan Indonesia, 2024)
This research aims to develop ECARsites, an online site designed to support data-related activities in science learning and to facilitate the implementation of data, computational thinking (CT), and self-directed learning (SRL) practices in a more contextualized and relevant way for students. The approach used design-based research (DBR) methods, focusing on developing high-quality learning products or systems that meet user needs. The study was conducted at MA X in Magetan, Indonesia, involving four middle school science teachers and eighteen middle school students. The research findings showed that DBR can be an effective method of professional development for science teachers, focusing on developing relevant and contextual innovations for students. Integrating data practices, CT, and SRL frameworks into the DBR process facilitated the development of students' scientific thinking skills, leading to a more immersive and appropriate science education for today's digital age. The study highlights the importance of using real data in teaching, involving students in data processing, and supporting teachers in designing and implementing data-driven learning. The study also emphasizes the importance of effective professional development in computational thinking and self-directed learning and the need for investment in long-term professional development programs to prepare teachers for an increasingly technology-dependent world of education.